2021
DOI: 10.3390/v13071250
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Pathogenesis of Nairobi Sheep Disease Orthonairovirus Infections in Sheep and Cattle

Abstract: Nairobi sheep disease orthonairovirus (NSDV) is a zoonotic tick-borne arbovirus, which causes severe gastroenteritis in small ruminants. To date, the virus is prevalent in East Africa and Asia. However, due to climate change, including the spread of transmitting tick vectors and increased animal movements, it is likely that the distribution range of NSDV is enlarging. In this project, sheep and cattle (hitherto classified as resistant to NSDV) were experimentally infected with NSDV for a comparative study of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…18,19 The ISH data demonstrate that KASV is hepatotropic, a feature shared by several bunyaviruses of public health and veterinary importance including CCHFV, NSDV, and Rift Valley fever virus. 9,16,28,31 The observed minor tropism for presumptive endothelial cells and Kupffer cells may promote more advanced liver disease due to direct and/or indirect effects of viral infection. Endotheliotropism and subsequent damage to the hepatic vasculature may also predispose to ascending bacterial infection from the gastrointestinal tract, as rare bacilli were observed in a 9 DPI bat with hepatic necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 The ISH data demonstrate that KASV is hepatotropic, a feature shared by several bunyaviruses of public health and veterinary importance including CCHFV, NSDV, and Rift Valley fever virus. 9,16,28,31 The observed minor tropism for presumptive endothelial cells and Kupffer cells may promote more advanced liver disease due to direct and/or indirect effects of viral infection. Endotheliotropism and subsequent damage to the hepatic vasculature may also predispose to ascending bacterial infection from the gastrointestinal tract, as rare bacilli were observed in a 9 DPI bat with hepatic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 Orthonairovirus-associated pathology in vertebrate hosts is understudied, and descriptions have thus far been limited to humans naturally infected with CCHFV, murine and nonhuman primate models of CCHF, sheep experimentally and naturally infected with NSDV, and mice experimentally infected with the 11SB23 strain of Leopards Hill virus (LPHV), a virus isolated from a giant leaf-nosed bats (Hipposideros gigas) in Zambia. 9,13,16,17 Gross and/or histological lesions in severe or fatal orthonairovirus infections include hepatopathy or hepatic necrosis, often with minimal inflammation, enteritis and/or gastrointestinal hemorrhage, and splenic lymphoid depletion and/or necrosis. 9,16,17 Severe systemic orthonairoviral disease can progress to widespread hemorrhaging, typified by CCHF in humans, and is hypothesized to be driven by a dysregulated immune response and strong tropism of these viruses for endothelium and cells of the mononuclear phagocyte system.…”
Section: Infectious Disease -Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Although mechanisms of transmission through migratory birds have been investigated for other viral diseases belonging to the genus Orthonairovirus, including the Crimean-Congo hemorrhagic fever virus [22,23], but no studies have been conducted to assess NSDV transmission based on migratory bird migration. Studies on NSD have mostly focused on classical epidemiological investigations and virological studies [11,24]. Krasteva et al [7] found that environmental factors such as soil moisture, livestock density, and precipitation act as key factors for NSDV circulation and pointed out Ethiopia, Malawi, Zimbabwe, Southeast China, Taiwan, and Vietnam as suitable regions for NSDV.…”
Section: Introductionmentioning
confidence: 99%
“…Besides ticks, DUGV appears capable of infecting various hosts including distinct arthropods, ruminants, rodents, monkeys, and birds [ 21 , 22 ]. DUGV and CCHFV have been classified in the Nairobi sheep disease orthonairovirus (NSDV) and CCHFV serogroups, respectively [ 23 , 24 , 25 ], with possible antibody cross-reactivities in some immunoassays [ 26 , 27 ]. However, our knowledge of human cell infection by DUGV remains very limited.…”
Section: Introductionmentioning
confidence: 99%